The limits of altruism and conflicts of values in the perception of cultural heritage of contemporary Croatia - Špikić, Marko (2013)
In the culture of conservation of the past century there were constant attempts to extend the magnitude of heritage values, but also to subject them to conscious and unconscious denial. This process of expansion, which could be seen as democratization of sensibility, implies another two processes: strengthening of tolerance towards different sorts of heritage (emancipation of values) and spatial extension of values (affirmation of the setting and of the marginal). In fin-de-siècle Central Europe and Italy these two principles were accompanied by a third, the principle of care (Pflege) for multi-layered monuments that had to substitute discriminatory interventionism of stylistic restoration. These new, “revelatory” conservation concepts were disputed as early as 1918 following large-scale war destructions, then also by modernist aesthetics and totalitarian politics ; finally, after 1945 by the revision of the conservation theory by extensive reconstructions and reformist concepts of the restauro critico. The newly democratic societies of Central, Eastern and South-Eastern Europe after 1989 evince different understandings of the concept of cultural heritage. In this paper I will discuss the Croatian experience of the past twenty years, bearing in mind the new trends arising in Central- and Eastern-European countries (the processes of oblivion and revitalizing of memory, reconstruction of “national monuments” and simultaneous discovery of “other” histories). Thus I will discuss the country’s post-war (post-1995) response to Riegl’s concept of altruism, previously considered by Croatian conservators around 1900, when in service of Austrian Zentralkommission. The questions discussed in the presentation will be: who are the bearers of values-expansion in conservation practice of post-1990 Croatia and how successful are they? Are there concrete limits to altruism following the over-emphasized national sentiment in the post-war reality and what are the problems caused by the clash of material and spiritual values in contemporary Croatia?